Swimming Exercise Management on Jaka Utama SC Lampung Club in the Covid-19 Pandemic - Putri, Anita Herdiana; Cahyadi, Ardian; Sitepu, Akor; Husein, Sudirman; Utama, Dimas Duta Putra (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
This study aims to determine the training management of the Jaka Utama SC Lampung swimming club during the covid-19 pandemic. The research was conducted using a descriptive qualitative survey method. Research data collection is carried out in natural conditions and primary data sources. The subjects used in this study were 12 subjects, including the Jaka Utama swimming club, two administrators, two coaches, four parents and four swimmers at Club Jaka Utama SC Lampung. This study uses a qualitative descriptive method with the research instrument based on observation, interviews and documentation. The research results explained that the Club Jaka Utama organization was running as it should during the covid-19 pandemic because the organizational and administrative systems were still simple and in the process of implementation, still complying with health protocols. The management system is unprofessional, with some administrators holding concurrent positions in the management structure. Coordination between administrators is natural following the circumstances. The training management at Club Jaka Utama SC Lampung has adapted to the conditions during the covid-19 pandemic, the organizational condition of Club Jaka Utama SC Lampung is not going well, and the management system has not undergone regular reorganization. Reports for athletes are carried out directly by the administrators and coaches; parents accompany children in training so that they witness the training process given.